Undocuments - Rivera, John-Michael, 1969- (Book collections on Project MUSE., 2021)
"UNDOCUMENTS is an expansive multi-genre exploration of Greater Mexican documentality that reveals the complicated ways all Latinx peoples, including the author, become objectified within cultures. John-Michael Rivera remixes the Florentine Codex and other documents as he takes an intense look at the anxieties and physical detriments tied to immigration."--